Methods of Analysis of Chaotic Behavior of Measurement Data of a Complex Energy System - Jankowski, P. (Scientific Journal of Gdynia Maritime University, 2018)
The article presents an example of chaotic behavior in a selected piece of the power network modeled by nonlinear system of differential equations. This article also discusses the most important aspects of identifying chaotic behavior in a system, based on only the recorded time course of one state variable without knowing the real dimension of the phase space.